Developing Pre-service English Teachers’ Critical Thinking by Using Academic Journal Writing 4.0 - Lilia Indriani (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2019)
Learning a foreign language is an integrated process of the four basic skills: listening, speaking, reading, and writing. As non-native English speakers, students are expected too much with their English even with the resource-poor EFL settings. Pre-service English teachers in Asia context make teaching becomes a really impossible job. Moreover, the wide spread of technology and pop culture make a new shift of paradigm in language teaching. Today, teachers and learners live in a technology-enhanced learning environment 4.0, and honestly, teachers are really difficult to catch up. Therefore, creativity and innovation in fostering TEFL is really needed. As pre-service teachers, they should intellectually have the abilities to conceptualize, apply, analyze, synthesize, and/or evaluate information gathered from, or generated by, observation, experience, reflection, reasoning, or communication, as a guide to belief and action that is why academic journal writing in edmodo would be one of the solution. This case study is about how to develop critical thinking by using academic journal writing for pre-service English teachers in TEFL class. They not only discuss about current issues in teaching and learning English but also combine technology, creativity and innovation.